EVALUASI TAHAPAN PUBLIC RELATIONS PROGRAM CORPORATE COMMUNICATION PT. XL AXIATA (STUDI KASUS PELAKSANAAN CSR XL FUTURE LEADERS TAHUN 2012-2016) - Wahyuni, Mentari Tryana; Pascarani, Ni Nyoman Dewi; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
Corporate Social Responsibility Program keep evolving and innovating in various companies in Indonesia, especially since it is defined as an obligation that set forth on Chapter V Article 74 of Law Number 40 Year 2007. XL Axiata is one of the largest telecommunication company in Indonesia that gives a special attention to its CSR program by creating CSR program titled